Balanced scorecard step-by-step : maximizing performance and maintaining results - Niven, Paul R. (Wiley, 2006)
PRAISE FOR Balanced Scorecard Step-By-Step: Maximizing Performance and Maintaining Results, Second Edition"As a practitioner and thought leader, Paul Niven is superbly bridging the gulf between BSC theory and application through hands-on experiences and real-world case studies.- Resumé vydavatel